Ammonium transformed into nitrous oxide via nitric oxide by Pseudomonas putida Y-9 under aerobic conditions without hydroxylamine as intermediate. (April 2019) - Huang, Xuejiao; Xu, Yi; He, Tengxia; Jia, Hongjie; Feng, Mi; Xiang, Shudi; Wang, Shutong; Ni, Jiupai; Xie, Deti; Li, Zhenlun
Graphical abstract: Highlights: NH4 + oxidized to N2 O by P. putida Y-9 without the accumulation of NH2 OH and NO2 − under aerobic conditions. NH2 OH inhibits the transformation efficiency of NH4 + to N2 O. NH4 + could accelerate the transformation of NH2 OH to NO2 − . Ammonia monooxygenase doesn't exist in P. putida Y-9. The ammonium oxidation pathway of P. putida Y-9 may be NH4 + → NO → N2 O. Abstract: Previous studies have reported that hydroxylamine (NH2 OH) is an inevitable intermediate of the ammonium (NH4 + ) oxidation pathway under aerobic conditions. In this study, Pseudomonas putida Y-9 was found to oxidize ammonium into N2 O via NO without the accumulation of NH2 OH and NO2 − under aerobic conditions. NH2 OH was nearly completely transformed into NO2 − whether NH4 + was present in the medium, and NH4 + could accelerate the transformation of NH2 OH to NO2 − by promoting Y-9 growth. NH4 + was oxidized rapidly by Y-9 with or without the presence of NH2 OH in the medium, and the decrease of total nitrogen reached 30.65 mg/L and 39.38 mg/L, respectively, which indicates that NH2 OH inhibits the transformation efficiency of NH4 + to N2 O. Gene amplification and enzyme assays demonstrated that ammonia monooxygenase doesn't exist in Y-9. All results show that NH4 + can be transformed into N2 O via NO by Y-9 under aerobic conditions without NH2 OH as intermediate.